Disease modeling of ADAMTS9-related nephropathy using kidney organoids reveals its roles in tubular cells and podocytes - Yu, Seyoung; Choi, Yo Jun; Rim, John Hoon; Kim, Hye-Youn; Bekheirnia, Nasim; Swartz, Sarah Jane; Dai, Hongzheng; Gu, Shen Linda; Lee, Soyeon; Nishinakamura, Ryuichi; Hildebrandt, Friedhelm; Bekheirnia, Mir Reza; et al. (Frontiers in Medicine, 2023)
Mutations in ADAMTS9 cause nephronophthisis-related ciliopathies (NPHP-RC), which are characterized by multiple developmental defects and kidney diseases. Patients with NPHP-RC have normal glomeruli with no or minimal proteinuria. Herein, we identified novel compound heterozygous ADAMTS9 variants in two siblings with NPHP-RC who had glomerular manifestations, including proteinuria. To investigate whether ADAMTS9 dysfunction causes NPHP and glomerulopathy, we utilized kidney organoid models. Results showed that ADAMTS9 knockout had no effect on nephron differentiation; however, it induced a decrease in the number of primary cilia, thereby recapitulating renal ciliopathy. Single-cell transcriptomics revealed that ADAMTS9 is highly expressed in podocyte clusters, followed by the proximal tubules. Loss of ADAMTS9 upregulated several signaling pathways, including the Wnt/PCP signaling pathway. In summary, our study provides insights into the functional roles of ADAMTS9 in glomeruli and tubules.